2007
DOI: 10.1016/j.diabet.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal glucose metabolism in patients treated with antipsychotics

Abstract: Second-generation (atypical) antipsychotic medications are of great benefit to a wide variety of people with psychiatric disorders, especially patients with schizophrenia. However, one constellation of adverse effects is an increased risk of obesity, diabetes, and metabolic syndrome. Increasing numbers of reports concerning impaired glucose tolerance, diabetes, and ketoacidosis have raised concerns about a possible association between abnormal glucose metabolism and treatment with atypical antipsychotics, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
11

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(93 citation statements)
references
References 48 publications
(84 reference statements)
2
80
0
11
Order By: Relevance
“…Several underlying mechanisms have been proposed to explain this intimate connection between psychiatric disorders and metabolic disturbances, including DM [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several underlying mechanisms have been proposed to explain this intimate connection between psychiatric disorders and metabolic disturbances, including DM [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a direct diabetogenic effect of clozapine could not be proven by these data, despite previous reports in other population groups suggesting such a direct effect. [8,20] It is possible that the high incidence of undiagnosed diabetes in our group may be attributable to other factors (e.g. family history, physical inactivity, abdominal obesity, poor diet).…”
Section: Discussionmentioning
confidence: 98%
“…[1] It has long been known that clozapine is associated with weight gain [3] and more recently it has also been shown that there is an increased risk among clozapine users for developing metabolic syndrome. [4][5][6][7] It has been suggested that clozapine may have a direct effect on glucose regulation, independent of weight gain, [8] and Koller et al [2] suggested a causal relationship between clozapine treatment and diabetes.…”
mentioning
confidence: 99%
“…The combined blockade of H1 and 5HT2C receptors has been especially associated with weight gain -sometimes profoundand could explain why atypical antipsychotics such as olanzapine and clozapine, which have high 5HT2C as well as H1 affinities, might have greater weight gain liabilities than an agent such as chlorpromazine, which lacks appreciable 5HT2C effects, even though it has H1 antagonist properties (Cutler et al, 2008;Kroeze et al, 2003). The high interindividual variability in medication-induced weight gain suggests that genetic factors influence the risk to gain weight (Holt and Peveler, 2009 (Scheen and De Hert, 2007;Okumura et al, 2010;Citrome et al, 2007), the risk being 1.3 fold higher in people with schizophrenia taking SGAs compared with those receiving FGAs (M. Smith et al, 2008). However, the risk of diabetes-related adverse events differs between SGAs.…”
Section: Treatments Exacerbate Cardiometabolic Risk Factorsmentioning
confidence: 99%